Consumptive Capacity Research Based on Wind-Solar Hybrid Characteristics - Linyan CHENG; Yanhong FENG; Lin XU (Zhongguo dianli)
The traditional wind power consumptive method does not adapt to the solution of consumptive capacity in the wind-solar hybrid area, a new method is therefore proposed in this paper to rapidly calculate the consumptive capacity of renewable energy in order to develop and utilize the wind and solar resources in a healthy way. Firstly, based on the existing wind and solar output data of a whole year in North Hebei area, the whole-year wind-solar hybrid output data are obtained according to the planned ratio of wind and solar power; and then, the effective output of wind and solar power in the same hour of a year is calculated; Finally, based on the power system’s peak shaving margin for every hour of three typical days, including the typical day in the summer and winter respectively and the small heating load day, the consumptive installed capacity of wind and solar power per hour is calculated, and the consumptive capacity of renewable energy is obtained through comparative analysis. Through a case study of South Zhangjiakou area in 2019, the effectiveness of the proposed method has been proved.